Photosynthetic and yield responses of rotating planting strips and reducing nitrogen fertilizer application in maize–peanut intercropping in dry farming areas - Han, Fei; Guo, Shuqing; Wei, Song; Guo, Ru; Cai, Tie; Zhang, Peng; Jia, Zhikuan; Hussain, Sadam; Javed, Talha; Chen, XiaoLi; Ren, Xiaolong; Al-Sadoon, Mohammad Khalid; et al. (Frontiers in Plant Science, 2022)
Improving cropping systems together with suitable agronomic management practices can maintain dry farming productivity and reduce water competition with low N inputs. The objective of the study was to determine the photosynthetic and yield responses of maize and peanut under six treatments: sole maize, sole peanut, maize–peanut intercropping, maize–peanut rotation–intercropping, 20% and 40% N reductions for maize in the maize–peanut rotation–intercropping. Maize–peanut intercropping had no land-use advantage. Intercropped peanut is limited in carboxylation rates and electron transport rate (ETR), leading to a decrease in hundred-grain weight (HGW) and increase in blighted pods number per plant (NBP). Intercropped peanut adapts to light stress by decreasing light saturation point (Isat) and light compensation point (Icomp) and increasing the electron transport efficiency. Intercropped maize showed an increase in maximum photosynthetic rate (Pnmax) and Icomp due to a combination of improved intercellular CO2 concentration, carboxylation rates, PSII photochemical quantum efficiency, and ETR. Compare to maize–peanut intercropping, maize–peanut rotation–intercropping alleviated the continuous crop barriers of intercropped border row peanut by improving carboxylation rates, electron transport efficiency and decreasing Isat, thereby increasing its HGW and NBP. More importantly, the maize–peanut rotation–intercropping had the land-use advantage. A 20% N reduction for maize in maize–peanut rotation–intercropping does not affect photosynthetic character and yield for intercropped crops. However, a 40% N reduction decreased significantly the carboxylation rates, ETR, Icomp and Pnmax of intercropped maize, thereby reducing HGW and grain number per spike and making land-use efficiency negative.